Mediasi Berbasis Al-Qur'an: Solusi Efektif untuk Mencegah Perceraian di Era Modern - Al Bawaniy, Embrizal; Taufiq, Muhammad (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2024)
This study aims to explore the effectiveness of Qur'an-based mediation in preventing divorce in the modern era and its relevance in the social and legal context of Indonesia. The research method employed is a qualitative approach with descriptive analysis, involving literature review and empirical data from religious courts. The findings reveal that Qur'an-based mediation, which emphasizes principles of justice, deliberation, and peace, is highly effective in resolving marital conflicts and reducing divorce rates. The use of technology in the form of e-mediation during the COVID-19 pandemic has also proven to enhance the accessibility and efficiency of the mediation process. The integration of Qur'anic mediation principles into the national legal system through supportive regulations, such as the Supreme Court Regulation No. 1 of 2016, strengthens the role of religious courts in family dispute resolution. Public education and training programs for mediators based on Qur'anic values are crucial steps to optimize the implementation of this mediation. In conclusion, Qur'an-based mediation is not only effective in preventing divorce but also strengthens family and societal harmony, demonstrating high relevance in the modern context.